Mortality rate after open Roux-in-Y gastric bypass: a 10-year follow-up - Bruschi Kelles,S.M. (2014)
The prevalence of obesity has increased to epidemic status worldwide. Thousands of morbidly obese individuals undergo bariatric surgery for sustained weight loss; however, mid- and long-term outcomes of this surgery are still uncertain. Our objective was to estimate the 10-year mortality rate, and determine risk factors associated with death in young morbidly obese adults who underwent bariatric surgery. All patients who underwent open Roux-in-Y gastric bypass surgery between 2001 and 2010, covered by an insurance company, were analyzed to determine possible associations between risk factors present at the time of surgery and deaths related and unrelated to the surgery. Among the 4344 patients included in the study, 79% were female with a median age of 34.9 years and median body mass index (BMI) of 42 kg/m2. The 30-day and 10-year mortality rates were 0.55 and 3.34%, respectively, and 53.7% of deaths were related to early or late complications following bariatric surgery. Among these, 42.7% of the deaths were due to sepsis and 24.3% to cardiovascular complications. Male gender, age ≥50 years, BMI ≥50 kg/m2, and hypertension significantly increased the hazard for all deaths (P<0.001). Age ≥50 years, BMI ≥50 kg/m2, and surgeon inexperience elevated the hazard of death from causes related to surgery. Male gender and age ≥50 years were the factors associated with increased mortality from death not related to surgery. The overall risk of death after bariatric surgery was quite low, and half of the deaths were related to the surgery. Older patients and superobese patients were at greater risk of surgery-related deaths, as were patients operated on by less experienced surgeons.